If I were you [videorecording (DVD)] - Carr-Wiggin, Joan; Harden, Marcia Gay; Watling, Leonor; Quinn, Aidan; Mahaffey, Valerie (Kino Lorber, 2013)
After Madelyn and Lucy meet by chance, they make a pact to fix their unhappy lives: they will only do what the other one says and ignore their own instincts. But Madelyn has a secret. She knows her husband is sleeping with Lucy, a much younger and beautiful woman. Madelyn's plan backfires when Lucy, an aspiring actress, orders her to play King Lear in a very amateur production with Lucy playing the fool.